Artistic and aesthetic experiences in the learning and development of pre-school children: contributions from the historical-critical pedagogy and historical-cultural psychology (Olhar de Professor, 2021)
In this investigation, it was assumed as the main objective understanding the artistic and aesthetic experiences for the learning and development of preschool children starting from a critical and contextualized bibliographic essay. In other words, the methodological design contemplated the dialogue with classical and current readings, having as a reference the historical-critical pedagogy and historical-cultural psychology, which in turn, allows (re)thinking the teaching and learning processes aiming at a sensitive and emancipatory human educational training. The results revealed that the teaching and learning process must be planned and systematized from broader intentions, with emphasis on the gnosiological, ontological and teleological dimensions, considering the relevance of the teacher in the organization of pedagogical practices in order to favor the appropriation and objectification of artistic knowledge on the behalf of the students inserted in the formative institutions of Early Childhood Education.
Keywords: Aesthetic Education; Arts teaching; Child education